2013
DOI: 10.1016/j.bpj.2012.11.930
|View full text |Cite
|
Sign up to set email alerts
|

Tension Induces a Base-Paired Overstretched DNA Conformation

Abstract: Type II topoisomerases maintain DNA topology by regulating the level of supercoiling of chromosomes. DNA gyrase is a unique and highly conserved bacterial Type II topoisomerase which is able to introduce negative supercoils into the genome. Using magnetic-tweezers, we assessed the supercoil generation and relaxation activities of Escherichia coli and Salmonella typhimurium DNA gyrases. Our results indicate that under single-enzyme conditions and 0.6-pN tension, both enzymes relax DNA at similar rates, but Salm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 0 publications
0
43
0
Order By: Relevance
“…Simulations have shown that whereas G-C pairs persist through the transition, A-T pairs often form melted bubbles (30,37). Similarly, various pulling experiments and theoretical models have also demonstrated that at low-to-moderate monovalent salt conditions (<150 mM), AT-rich sequences tend to melt more easily than GC-rich sequences (24,28,29,(65)(66)(67)(68)(69), whereas under high-salt conditions interstrand charge repulsion is reduced, and AT-rich sequences also form S-DNA (31,32). Moreover, cyclic pulling experiments demonstrate that force-induced melting is associated with hysteresis, such that once melted, the complementary strands reanneal slowly (21,28,32,70).…”
Section: High-force Regime: Dap Substitution Decreases the Tension Atmentioning
confidence: 98%
See 2 more Smart Citations
“…Simulations have shown that whereas G-C pairs persist through the transition, A-T pairs often form melted bubbles (30,37). Similarly, various pulling experiments and theoretical models have also demonstrated that at low-to-moderate monovalent salt conditions (<150 mM), AT-rich sequences tend to melt more easily than GC-rich sequences (24,28,29,(65)(66)(67)(68)(69), whereas under high-salt conditions interstrand charge repulsion is reduced, and AT-rich sequences also form S-DNA (31,32). Moreover, cyclic pulling experiments demonstrate that force-induced melting is associated with hysteresis, such that once melted, the complementary strands reanneal slowly (21,28,32,70).…”
Section: High-force Regime: Dap Substitution Decreases the Tension Atmentioning
confidence: 98%
“…For WT-DNA in physiological salt conditions, the characteristic overstretching transition around 60 pN is caused by a combination of factors, including force-induced melting (through strand peeling and melting bubble formation) and adoption of the S-DNA conformation (24,32,65,70,80). Several studies have shown that forceinduced melting tends to originate at AT-rich regions (28)(29)(30)37). In particular, a detailed study conducted by Bosaeus et al comparing the overstretching behavior of short 70% AT and 60% GC oligonucleotides (oligos) found that whereas AT sequences melt and GC sequences form S-DNA, the transition threshold for GC oligos was similar if not slightly higher than AT oligos: 63.3 5 1.1 pN for GC versus 61.5 5 2.6 pN for AT (28,29).…”
Section: Dap Substitution Flexurally Stiffens Dna Yet Lowers the Barrmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis for a switch from a helical form to a ladder‐type structure has also been proposed for the transition occurring in DNA in stretching experiments at about 60–70 picoNewton (pN) of applied force, for which a ladder‐type structure (named S‐DNA) was proposed on the basis of experimental data and molecular dynamics (MD) calculations . Although the existence of this hypothetical structure has been subsequently questioned by other authors, on the basis of an alternative model of partial denaturation under tension, hydrogen‐bonded overstretched states of DNA have been found to be formed for GC‐rich sequences, where they probably play an important role in some biological processes such as in DNA recombination …”
Section: Resultsmentioning
confidence: 99%
“…58 Although the existence of this hypothetical structure has been subsequently questioned by other authors, on the basis of an alternative model of partial denaturation under tension, 59,60 hydrogen-bonded overstretched states of DNA have been found to be formed for GC-rich sequences, where they probably play an important role in some biological processes such as in DNA recombination. 61 Interestingly, X-ray diffraction or NMR experiments by other authors have pointed out as well that PNA can adopt a broad range of structural motifs in duplexes. 62,63 For example, a modulation of the PNA:PNA helicity was demonstrated by Renikuntla and Armitage.…”
Section: Mode Of Interaction In the Modified Pna:pna Duplexesmentioning
confidence: 99%